Standard Test Methods for Determining the Izod Pendulum Impact Resistance of Plastics - Astm
These test methods cover the determination of the resistance of plastics to "standardized" (see Note 1)pendulumtype hammers, mounted in "standardized" machines, in breaking standard specimens with one pendulum swing (see Note 2). The standard tests for these test methods require specimens made with a milled notch (see Note 3). In Test Methods A, C, and D, the notch produces a stress concentration that increases the probability of a brittle, rather than a ductile, fracture. In Test Method E, the impact resistance is obtained by reversing the notched specimen 180° in the clamping vise. The results of all test methods are reported in terms of energy absorbed per unit of specimen width or per unit of cross-sectional area under the notch. (See Note 4.)
Keywords: IZOD PENDULUM IMPACT RESISTANCE OF PLASTICS